The Effect of Religiosity on Purchase Intention of Luxury Brands Moderating Impact of Brand Addiction - Riandy Mardhika Adif; Irsadunas; Salsabila Putri Marsya; Sobrina Alfatah; Widya Putri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to analyze the influence of religiosity on luxury brand purchase intentions among working women in Banda Aceh and explore the role of brand addiction as a moderating variable. Data was obtained from 95 respondents who met the criteria and analyzed using Structural Equation Modeling (SEM) with PLS. The results show that religiosity has a negative but not significant influence on luxury brand purchase intentions. However, when brand addiction is used as a moderating variable, religiosity has a positive and significant influence on luxury brand purchase intention. This indicates that brand addiction can strengthen the relationship between religiosity and purchase intention. This shows that women with religious tendencies but experiencing brand addiction tend to still have the intention to purchase luxury products. These findings imply that although religiosity typically decreases luxury brand purchase intentions, brand addiction may alter this effect, encouraging religious consumers to participate in luxury brand consumption. Practical implications of these results include understanding that psychological factors such as brand addiction are capable of influencing purchasing decisions despite religious norms and beliefs. This research recommends further exploration of other factors that may play a role, such as social status and peer influence, to gain deeper insight into consumer behavior in the social and cultural environment of Banda Aceh.